Econometric Analysis. - Greene, William H. (Delhi, Pearson Education, 2006)
Includes Classical, Bayesian, GMM, maximum likelihood, cross section, and more time series and panel data, covering applications and numerical examples. This book gives solutions to applications that show students how to do the computations. It gives attention to both linear and nonlinear techniques.
Include Bibliography Reference and Index Material.
Keywords: Econometrics; Econometric analysis; least squares